Asymptomatic right ventricular dysfunction in surgically repaired adult tetralogy of fallot patients - Krishna Kumar Mohanan Nair; Sanjay Ganapathi; Bijulal Sasidharan; Anees Thajudeen; Harikrishnan Sivadasan Pillai; Jaganmohan Tharakan; Thomas Titus; Ajitkumar Valaparambil Kumaran; Sivasankaran Sivasubramonian; Kavassery Mahadevan Krishnamoorthy (Wolters Kluwer Medknow Publications, 2013)
Background: Right ventricular (RV) dysfunction after surgical repair of Tetralogy of Fallot (TOF) is often asymptomatic and may be detected by tissue Doppler imaging (TDI). The severity of RV dysfunction is more after intracardiac repair with transannular patch (TAP). Methods: One hundred seventy-three adult patients who have undergone surgical repair for TOF were prospectively analyzed for RV function using 2D echocardiography and TDI. RV function was compared between patients who have undergone intracardiac repair with and without TAP. Results: In both the patient sub-groups, TDI derived myocardial performance index (MPI) and myocardial velocities were abnormal even when 2D echocardiography derived RV functional area change was normal. TDI derived MPI was significantly higher (0.5 ± 0.1 vs. 0.4 ± 0 P0 < 0.001) and Systolic tricuspid annular velocity (Sa) (9.2 ± 1.3 vs. 10.8 ± 1.6 P < 0.001) was significantly lower in the TAP group. Older age at surgery and severity of pulmonary regurgitation on follow-up were among the significant predictors of TDI derived MPI. Conclusions: Asymptomatic RV dysfunction in surgically repaired adult TOF atients can be detected by TDI. Extent of RV dysfunction was significantly greater with patients requiring TAP, in those operated at older age, and in patients with severe pulmonary regurgitation.